2023
DOI: 10.1002/ece3.9909
|View full text |Cite
|
Sign up to set email alerts
|

Audience effects in a group‐living bird: How contact call rate is affected by vegetation and group size and composition

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…The social context is also likely to modulate the emission of contact calls. Swinhoe's White-eyes (Zosterops simplex), for instance, change their contact calling rates with experimental modifications of group size [75]. Meerkats (Suricata suricatta) adjust their calling rates to the number and distance of neighbours [44].…”
Section: Discussionmentioning
confidence: 99%
“…The social context is also likely to modulate the emission of contact calls. Swinhoe's White-eyes (Zosterops simplex), for instance, change their contact calling rates with experimental modifications of group size [75]. Meerkats (Suricata suricatta) adjust their calling rates to the number and distance of neighbours [44].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum count per minute can also be indicative of cue rates. Contact calls, which is the vocalization type we used for the tanager, are used for cohesion and movement coordination within groups (Kondo & Watanabe, 2009), and are associated with social contexts (Radford & Ridley, 2008), rather than with environmental conditions (Meaux et al., 2023). Consequently, we reasoned that a direct effect of habitat disturbance on cue rates would be unlikely in this species.…”
Section: Discussionmentioning
confidence: 99%
“…However, an indirect effect, mediated through group size, could be possible. It has been shown that individuals increase their cue rates in contact calls with increasing group size (Meaux et al., 2023; Striedter et al., 2003). Thus, in the tanager, the lower values of MAX observed at sites with greater anthropogenic habitat disturbance might represent a combination of smaller group sizes due to family members not rejoining and decreased cue rates due to smaller group sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation